(untitled) (Лучшие интеллектуальные исследования, 2025)
ABSTRACT: This article addresses the development of speaking competence, focusing on enhancing students’ abilities to engage in oral communication. It explores how speaking competence is shaped by listening comprehension and how teaching strategies for monologic, dialogic, and polylogic speech—through both inductive and deductive methods—contribute to the development of oral speech competence.